Biocompatibility of a novel hydroxyapatite-based endodontic sealer enriched with silicon and strontium ions in rats - Mina Zarei; Maryam Javidi; Negar Bahrami-Taghanaki; Mina Bagheri; Maryam Peighoun (Mashhad University of Medical Sciences, 2024)
Objective: This study aimed to evaluate the biocompatibility of a novel bioceramic endodontic sealer formulation, combining tricalcium silicate/dicalcium silicate, silicon hydroxyapatite, and strontium hydroxyapatite.Methods: Sixty polyethylene tubes were filled with the following four materials (n = 15): AH Plus sealer, Sure-Seal Root bioceramic sealer, an experimental bioceramic sealer, and empty control tubes. Fifteen adult Wistar rats were used, each receiving all four tube types implanted subcutaneously on the dorsal skin. The rats were divided into three groups, evaluated at 15, 30, and 60 days postoperation.  Histological analysis assessed inflammation, fibrous capsule thickness, giant cell infiltration, and biomineralization. The Kruskal-Wallis test was used for statistical analysis, with the significance level set at P < 0.05.Results: There were no statistically significant differences in tissue reaction measures among the groups (P > 0.05). Intragroup comparisons revealed a significant reduction in inflammation in the AH Plus group (P = 0.04). Fibrous capsule thickness and giant cell infiltration decreased significantly in the Sure-Seal Root and AH Plus groups over the experiment (P< 0.05). Biomineralization increased in the experimental sealer group but without statistical significance (P > 0.05).Conclusions: Sure-Seal Root and AH Plus sealers exhibited significant decreases in some tissue reactions over time, but the experimental sealer did not. Despite the lack of statistical significance in between-group comparisons, the biocompatibility of commercially available sealers appears to be better than the experimental sealer, based on the results of this study.